Peningkatan Kehalusan Produk Pada Industri Kecil Cetakan Dengan Pendekatan Eksperimental - Yohanes T. Wibowo (CV. Multi Kreasi Media, 2024)
Nowadays, the efficiency of CNC milling machines has become one of the crucial issues in the industry in general and especially in small industries. This is due to high utilization but not efficiency. Low machine efficiency has an impact on the financial aspects of the industry. In addition to the issue of efficiency, the uncertainty of machining results is also a major issue because of its impact on time, cost, and large customer trust. Failure to achieve surface roughness results in rework, overtime, replacing materials, and starting the process from the beginning, all of which end in replacing materials and starting the process from the beginning, all of which end in costs. Through joint activities between industry and academia, an experiment was designed to experiment to improve the quality of the product surface and ensure that the product specifications are achieved. With this activity, machining parameters were obtained that could convincingly produce the target surface roughness. A total of 6 specimens were tested, and achieved 100% as targeted.